Left ventricular global longitudinal strain in patients treated with immune checkpoint inhibitors - Celebi Coskun, Ece; Coskun, Alper; Sahin, Ahmet Bilgehan; Levent, Fatih; Coban, Eyup; Koca, Fatih; Sali, Seda; Demir, Omer Furkan; Deligonul, Adem; Tenekecioglu, Erhan; Cubukcu, Erdem; Evrensel, Turkkan; et al. (Frontiers in Oncology, 2024)
BackgroundImmune checkpoint inhibitors (ICI) are generally associated with rare cardiac side effects, yet instances like myocarditis can be fatal. Therefore, detecting and managing left ventricular dysfunction early in ICI therapy is vital.ObjectivesThis study aims to evaluate whether left ventricular global longitudinal strain (LV GLS) is a predictor for early detection of cardiac dysfunction in patients receving ICI.MethodsThis retrospective cohort study included 44 cancer patients who received ICI therapy and underwent pre- and post- treatment assessments of left ventricular ejection fraction (LVEF) and LV GLS between May 2022 and November 2023. Retrospective comparisons and evaluations were conducted on pre-treatment and 3-month interval LVEF and LV GLS measurements during the first year of treatment.ResultsThe median follow-up duration was 5.3 months (0.5-18.9). No statistically significant difference between baseline and subsequent time points was observed in LVEF and LV GLS values (p>0.05). At the 3-month evaluation, a notable decrease in LVEF and LV GLS was observed in two patients. One patient with reduced LVEF and LV GLS succumbed to myocarditis, and another experienced sudden death of unknown etiology. The other two patients had decreased LV GLS with normal LVEF. Subsequent follow-ups of the patients exhibiting decreased LV GLS alone revealed no further decline in LVEF or LV GLS.ConclusionIn our study, a reduction in LV GLS did not demonstrate a significant role in the early prediction of ICI-related myocarditis or cardiac dysfunction. Further validation through multicenter, large-scale, prospective studies with extended follow-up periods is needed to confirm these findings.